The Importance of Personal Characteristic in Shaping Positive Perceptions of Organizational Climate in Universities - Kartika Nuradina; Pratidina Ekanesia; Squall Fikri Athallah; Riki Mukin (West Science Interdisciplinary Studies, 2023)
The purpose of this study is to provide a conceptual framework regarding organizational climate. Researches and theory regarding Organizational Climate began in 1968 and is still being researched until 2023. Most studies show that organizational climate has an influence on work performance in organizations, such as productivity, performance, job satisfaction, organizational commitment and organizational citizenship behavior. However, several studies have shown results with very low significance. This research will explain the importance of personal characteristics in forming a positive perception of the organizational climate especially in the university.